Molecular cloning and expression analysis of CONSTANS-LIKE 2 in Mucuna bracteata in different tissues and at low temperature - Misfahulhairah, Shariff; Namasivayam, Parameswari; Mohd-Yusoff, Nur Fatihah (World Researchers Associations, 2023)
Mucuna bracteata is a leguminous cover crop that is planted in Malaysian oil palm and rubber plantations. This legume can grow well locally but is unable to produce flowers. Non-flowering M. bracteata plants presumably do not perceive the flowering signals to initiate the reproductive phase due to environmental differences. This study is on cloning a putative flowering gene, CONSTANS-LIKE 2 (COL2), from leaves of M. bracteata. To understand the molecular regulation of this gene in locally grown M. bracteata, we analysed its expression profile in different tissues of M. bracteata seedlings and response to low temperature using real-time polymerase chain reaction. The MbCOL2 gene was identified to be expressed in all selected tissues; leaf, terminal bud and stem of 2 months, 6 months and 12 months-old seedlings in different patterns. The MbCOL2 expression was the highest in the leaf tissue. Meanwhile, the expression of MbCOL2 was increased due to the low temperature. Physicochemical properties of MbCOL2 and its orthologues were also defined to analyse their protein functional properties. Outputs from this study can assist to better understand the molecular regulation of growth and development in M. bracteata.